Effectiveness of multistimulation approach on feeding habits of low-birth-weight babies-A randomized control trial - Deepa Negi; Dharitri Swain; Tapas Kumar Som (Elsevier, 2022)
Introduction: Low- birth- weight neonates face oral feeding difficulties due to hemodynamic instability, immaturity of central nervous systems, and incomplete development of oral functions. Use of several interventions might help in improvement of the feeding ability of neonates. The objective of the study was to evaluate the effect of the multistimulation approach in low-birth-weight babies on the oral feeding performance, oral intake volume, weight gain and transition time from tube to total oral intake. Methods: A Randomized, parallel-group, multiple arm trial study was conducted, and a total of 44 low birth weight babies were randomized into three parallel groups with a 2:1:1 ratio. Babies who are Hemodynamically stable were included in the trial. In two Intervention groups, one received an oral stimulation program, another intervention group received tactile stimulation, and the control group received routine newborn procedures for the same duration of time. Oral feeding performance was determined by Oral Feeding Skills (OFS) on a daily basis for five days after providing ten days of intervention. Neonates were monitored until hospital discharge. Results: Infants in the stimulation groups had significantly better oral feeding performance than infants in the control group in terms of mean proficiency, transfer rate and overall transfer of feeding volume. There was a substantial increase in mean feeding score, daily weight, oral intake volume, and early transition time in both intervention groups compared to control. There was no significant difference in feeding behaviours between the oromotor and multistimulation groups, but the multistimulation group gained more weight compared to the oromotor group. Conclusions: Infants exposed to the stimulation programme had better feeding skills and a shorter transition period from tube feeding to oral feeding; however, the babies who received multistimulation gained greater weight than babies who received only oromotor stimulation. The study recommends multi stimulation in the form of oromotor, and tactile stimulation can be used as an effective NICU procedure for maintaining an infant's ability to take feeds orally before being discharged from the hospital.